(untitled) (Journal of the College of Basic Education, 2022)
The current research dealt with the subject of artistic treatments for the light image and its role in graphic design, given the effective role the image plays in the covers of magazines and how to treat it in the best way to attract the attention of the recipients. The problem of the research lies in the presence of a clear deficiency in the processing of the image used in the designs of the covers of Iraqi magazines compared to the foreign ones to improve the design reality in Iraq, and that there is a weakness in the designer’s information about the artistic treatments of the image, and from here the following question was raised in the research problem: